2019
DOI: 10.1039/c9bm00868c
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillar fibronectin plays a key role as nucleator of collagen I polymerization during macromolecular crowding-enhanced matrix assembly

Abstract: PAPER Viola Vogel et al. Fibrillar fi bronectin plays a key role as nucleator of collagen I polymerization during macromolecular crowding-enhanced matrix assembly Volume Macromolecular crowding is used by tissue engineers to accelerate extracellular matrix assembly in vitro, however, most mechanistic studies focus on the impact of crowding on collagen fiber assembly and largely ignore the highly abundant provisional matrix protein fibronectin. We show that the accelerated collagen I assembly as induced by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 73 publications
0
26
0
1
Order By: Relevance
“…Whereas FN is typically transiently present in acute phases of wound healing and tissue remodeling events, collagens are ECM molecules which are resistant to proteolytic cleavage from broad-spectrum proteases such as trypsin and pepsin, and persist in tissues as major structural components and major determinants of tissue stiffness [ 14 ]. Careful studies of composite FN and collagen matrices in vitro have demonstrated that FN binds collagen mainly under low tension, and as the matrix matures, two independent networks form, and the collagen matrix becomes the primary tension bearing element in the mature composite ECM [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas FN is typically transiently present in acute phases of wound healing and tissue remodeling events, collagens are ECM molecules which are resistant to proteolytic cleavage from broad-spectrum proteases such as trypsin and pepsin, and persist in tissues as major structural components and major determinants of tissue stiffness [ 14 ]. Careful studies of composite FN and collagen matrices in vitro have demonstrated that FN binds collagen mainly under low tension, and as the matrix matures, two independent networks form, and the collagen matrix becomes the primary tension bearing element in the mature composite ECM [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to Ficoll ® , the highest (over the non-MMC control) collagen type I deposition was only observed at day 4. Although one study has shown the Ficoll ® cocktail to result in lower collagen deposition than the non-MMC group after 14 days in human neonatal fibroblast cultures [ 36 ], most studies have shown the Ficoll ® cocktail to enhance collagen type I deposition in various cell populations (e.g., human skin fibroblasts [ 91 ], human corneal fibroblasts [ 31 ], human lung and skin fibroblasts [ 13 ], human bone marrow stem cells [ 79 ] and human ADSCs [ 80 ]), albeit at slower rates than sulphated polysaccharides [ 14 , 50 ]. Finally, HA had no effect on collagen type I deposition at any timepoint, independently of the concentration and molecular weight.…”
Section: Discussionmentioning
confidence: 99%
“…collagen fibrillogenesis (Graham et al, 2019). Additionally, FRET-FN has been used to investigate FN conformation in cancer malignancy, which revealed matrix stiffening and proangiogenic effect of the early interaction between unfolded FN and collagen near breast cancer cells (Wang et al, 2015(Wang et al, , 2017.…”
Section: Mechanical Force Fret Biosensormentioning
confidence: 99%
“…Förster or fluorescence resonance energy transfer-FN has also been employed to visualize FN conformational changes upon adsorption to the surface of materials with varying hydrophobicity, which revealed more extended FN conformation and better cell attachment on hydrophilic materials ( Baugh and Vogel, 2004 ). Applying this FRET-FN probe, more recent research revealed the co-localization of collagen I and relaxed FN ( Kubow et al, 2015 ), transformation of FN-coated collagen during force-mediated 3D tissue remodeling ( Legant et al, 2012 ), spatial variations of FN conformation in a 3D in vitro model ( Foolen et al, 2016 ), and the upregulation of low-tension FN by Ficoll crowding that promotes collagen fibrillogenesis ( Graham et al, 2019 ). Additionally, FRET-FN has been used to investigate FN conformation in cancer malignancy, which revealed matrix stiffening and pro-angiogenic effect of the early interaction between unfolded FN and collagen near breast cancer cells ( Wang et al, 2015 , 2017 ).…”
Section: Fret Biosensor and Mechanobiologymentioning
confidence: 99%